The Changing Landscape of Journalology in Medicine - Wilson, Mitch; Moher, David (Université d'Ottawa | University of Ottawa, 2018)
In the early 1970s, when Seminars in Nuclear Medicine started publication, little was known about the quality of reporting in biomedical journals. Senior scholars were invited to become scientific editors of journals based on their research credibility and stature. Their knowledge of journalology (publication science) was not assessed. Similarly, while the use of peer review was gaining momentum, there was limited guidance on the tasks and expectations of peer reviewing. Almost fifty years later the evidence base regarding the quality of reporting is vast. This paper highlights some of this evidence including that relevant to imaging and nuclear medicine research. In biomedical publications there is a crisis in reproducibility; high prevalence rates of reporting biases, such as selective outcome reporting; spin; low registration rates of research protocols; and endemic poor reporting of research across biomedicine. These issues and some more immediate solutions are also discussed in the paper. The use of reporting guidelines has been shown to be associated with better reporting of clinical trials and other research articles. The use of audit and feedback tools is likely to provide an important gauge about the functions of biomedical journals. Finally, the push to better equip scientific editors and peer reviewers is taking a more concerted effort.